Methods for Assessing the Accuracy of Video Camera Gyroscopic Stabilization Systems on a Moving Object - V. V. Matveev; I. A. Behler; E. I. Ponitkov; M. G. Pogorelov (Приборы и методы измерений)
Video camera, are installed on platforms of gyroscopic stabilization systems in order to improve the quality of visual information and provide the required orientation of the optical axis. The goal of the work was to develop a mathematical description that allows evaluating accuracy of gyroscopic stabilization systems for a video camera on a moving object, built on micromechanical sensors for primary information. A biaxial system for gyroscopic stabilization of a video camera on a moving object is considered. A mathematical description of the channel of the stabilization system with control over angle and angular velocity is given. Measuring the angle of deviation of the platform from the horizontal plane and its angular velocity is provided by micromechanical accelerometers and gyroscopes, respectively. Physical nature of the synchronous errors' occurrence in the stabilization system during angular vibrations of a moving object is explained. An assessment of the synchronous error of the stabilization system when the object oscillates with a frequency of 30 Hz is given. An analytical relationship is presented for estimating of the stabilization system errors is caused by random errors of gyroscopes and accelerometers. It is shown that if the platform is stabilized only by gyroscope signals containing random errors such as white noise in the measurements, this will lead to the platform drifting with a standard deviation proportional to the square root of time. In this case, the constant disturbing moment is not processed. A mathematical description of the “blurring” of the video camera image during platform vibrations caused by random errors in inertial sensors is given. Effect of image blur for various platform oscillation parameters is illustrated.